2017
DOI: 10.1016/j.tcr.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment of periprosthetic femur fractures around metaphyseal short stems – A feasible option?

Abstract: Periprosthetic femoral fractures are rare but significant events following total hip replacement. Metaphyseal short stems have recently been popularized as a bone preserving alternative to conventional uncemented total hip replacement. We present two periprosthetic femur fractures which occurred around two different metaphyseal uncemented stem designs. Successful conservative treatment was possible in both cases achieving bony union and excellent clinical results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Az egyik betegnél Proxima® (DePuy, Leeds, UK), másik betegnél Metha® (B. Braun Aesculap, Tuttlingen, Németország) rövid szárú protézis került beültetésre. Mindkét esetet konzervatív úton kezelték: teljes csontos átépülést és kitűnő klinikai eredményeket értek el (15).…”
Section: Megbeszélésunclassified
“…Az egyik betegnél Proxima® (DePuy, Leeds, UK), másik betegnél Metha® (B. Braun Aesculap, Tuttlingen, Németország) rövid szárú protézis került beültetésre. Mindkét esetet konzervatív úton kezelték: teljes csontos átépülést és kitűnő klinikai eredményeket értek el (15).…”
Section: Megbeszélésunclassified
“…Finally, PC stems particular architecture and load distribution onto the proximal femur may put them at risk of intraoperative periprosthetic fracture (IPPF). 7 After treating 142 cases with the CFP stem (Waldemar Link GmbH, Hamburg, Germany), Li et al 8 have reported a 7% rate of IPPF of the lateral femoral cortex located at the tip of the stem.…”
mentioning
confidence: 99%